PENGARUH KONSENTRASI LARUTAN EKSTRAK DAUN LIDAH MERTUA TERHADAP ABSORBANSI DAN TRANSMITANSI PADA LAPISAN TIPIS - Sunardi Sunardi; Kartika Sari (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
It has done research on the effect of the extract solution concentration in-law tongue (Sansevieriatrifasciata) on the absorbance and transmittance in thin layers. Experimental research is that by extracting the leaves of the tongue-in-law to obtain a dye. Then made a solution with a concentration of 1%, 2%, 3%, 4%, 5%, 6% and7%, and also made merua pure aloe extract solution, a solution of TiO 2, and a mixture of both. Characterization of a solution made with UV-Vis spectrometer 1800 which aims to determine the value of absorbance and transmittance. Spectrometer set at a wavelength of 411nm- 665 nm and an absorbance range 0-3. The results show that there is a relationship between the concentration of the absorbance by the equation A = 22,9c + 0.1946. The greater the concentration used, the greater the smaller the value of absorbance and transmittance values. The maximum absorbance obtained at a wavelength Î» = 411 nm and Î» = 665 nm while the absorbance value and the maximum trasmitansi respectively 3,58 and 1,433. . Key words:leaf extract in-law tongue (Sansevieriatrifasciata), absorbance, transmittance.